Genome-wide association study for Chagas Cardiomyopathy identify a new risk locus on chromosome 18 associated with an immune-related protein and transcriptional signature - Ester Cerdeira Sabino; Lucas Augusto Moysés Franco; Gabriela Venturini; Mariliza Velho Rodrigues; Emanuelle Marques; Lea Campos de Oliveira-da Silva; Larissa Natany Almeida Martins; Ariela Mota Ferreira; Paulo Emílio Clementino Almeida; Felipe Dias Da Silva; Sâmara Fernandes Leite; Maria do Carmo Pereira Nunes; et al. (PLoS Neglected Tropical Diseases, 2022)
Background Chronic Chagas Cardiomyopathy (CCC) usually develops between 10 and 20 years after the first parasitic infection and is one of the leading causes of end-stage heart failure in Latin America. Despite the great inter-individual variability in CCC susceptibility (only 30% of infected individuals ever present CCC), there are no known predictors for disease development in those chronically infected. Methodology/Principal findings We describe a new susceptibility locus for CCC through a GWAS analysis in the SaMi-Trop cohort, a population-based study conducted in a Chagas endemic region from Brazil. This locus was also associated with CCC in the REDS II Study. The newly identified locus (rs34238187, OR 0.73, p-value 2.03 x 10−9) spans a haplotype of approximately 30Kb on chromosome 18 (chr18: 5028302–5057621) and is also associated with 80 different traits, most of them blood protein traits significantly enriched for immune-related biological pathways. Hi-C data show that the newly associated locus is able to interact with chromatin sites as far as 10Mb on chromosome 18 in a number of different cell types and tissues. Finally, we were able to confirm, at the tissue transcriptional level, the immune-associated blood protein signature using a multi-tissue differential gene expression and enrichment analysis. Conclusions/Significance We suggest that the newly identified locus impacts CCC risk among T cruzi infected individuals through the modulation of a downstream transcriptional and protein signature associated with host-parasite immune response. Functional characterization of the novel risk locus is warranted. Author summary Chronic Chagas Cardiomyopathy (CCC) usually develops between 10 and 20 years after the first parasitic infection and is one of the leading causes of end-stage heart failure in Latin America. Despite the great inter-individual variability in CCC susceptibility, there are no known predictors for disease development in those chronically infected. We describe a new susceptibility locus for CCC through a GWAS analysis in the SaMi-Trop cohort, a population-based study conducted in a Chagas endemic region from Brazil. The newly identified locus on chromosome 18 is also associated with 80 different traits, most of them blood protein traits significantly enriched for immune-related biological pathways. Finally, we were able to confirm, at the tissue transcriptional level, the immune-associated blood protein signature using a multi-tissue differential gene expression and enrichment analysis. We suggest that the newly identified locus impacts CCC risk among T cruzi infected individuals through the modulation of a downstream transcriptional and protein signature associated with host-parasite immune response.